Knowledge and public health practices during lockdown towards COVID-19 in Bangladesh - Sharmin Akhtar; Rubel Ahmed; Sharmin Jahan; Md Mosharaf Hossain (International Journal of Public Health Science (IJPHS), 2021)
The study aimed to assess the role of having knowledge and essential hygiene practices to prevent coronavirus pandemic and to find out the relationship between people’s knowledge and good hygiene practices with socio-demographic variables during coronavirus disease 2019 (COVID-19) pandemic situation. In this study, data were collected from 248 respondents for cross-sectional study using voluntary response sampling from April, 30 2020 to May, 30 2020, during lockdown situation in Bangladesh. Descriptive statistics were done to calculate the frequencies and percentages by using Stata SE 14.2 (StataCorp). Chi-square was performed at the significance level of 5% to find the factors which were associated with knowledge about COVID-19. After knowing about COVID-19, 86.29% respondents had taken preventive measures and 71.37% respondents had agreed to stay at home. Among the respondents, 47.98% were involved in services and were positively associated with good general knowledge of preventive practices. Our present findings indicated significant relationship between good general knowledge and practice of general people towards COVID-19 outbreak in Bangladesh. The findings of the study are helpful for the researchers and the population to follow all good promotional practices for preventive measures against coronavirus.